The Effect of Visual Aid on Students’ Listening Comprehension - Nurul Aliyatul Khoiriyah; Yeni Mardiyana Devanti; Muhlisin Rasuki (Empat Sembilan Publisher, 2024)
Listening is essential for language development, underpinning skills like speaking, reading, and writing. Effective media choice in teaching is crucial since research emphasizes that comprehensible input and active engagement are vital for listening comprehension (Richards, 2008; Sadiku, 2015; Vandergrift, 1999). Harmer (2007) asserts that engaging with input is key for language activation, while recent studies (Danxin Liang, 2013; Chen Chan et al., 2014) suggest that audiovisual materials enhance comprehension by providing visual stimuli that aid attention and schema activation. This study explores how animated videos affect listening comprehension among 16 senior English language education students at Universitas Muhammadiyah Jember. Participants were exposed to both video and audio materials on nostalgia and melancholy, respectively, and answered 10 multiple-choice questions for each type. Analysis using a dependent sample t-test revealed no significant difference between the audio-only and video conditions, with a t-value of -0.522, a p-value of 0.609, and minimal effect sizes (Cohen's d of -0.131 and Hedges' g of -0.124). Despite theoretical support from dual-coding and multimedia learning theories, the study found negligible benefits from visual aids. Possible influencing factors include learner proficiency, content complexity, cognitive load, and low motivation.